Meeting the UK Government's prevention agenda: primary care practitioners can be trained in skills to prevent disease and support self-management. (May 2022) - Lawrence, W; Watson, D; Barker, H; Vogel, C; Rahman, E; Barker, M
Aims: The NHS Long Term Plan has a prevention focus and ambition to support patients to self-manage disease through improving health behaviours. An essential requirement of self-management is behaviour change, but many practitioners have not been trained in skills to support behaviour change. 'Healthy Conversation Skills' (HCS) training was developed at the University of Southampton for this purpose. This article reports on a pilot study that aimed to assess the feasibility of primary care practitioners adopting HCS in their routine practice. It describes their experiences and level of competence post-training. Methods: Health Education England (Wessex) commissioned HCS training for 18 primary care practitioners. Fifteen of these practitioners were subsequently observed in their consultations at one or two time points; face-to-face semi-structured, reflective feedback interviews were conducted immediately following the observations. Practitioners' HCS competence was assessed from the observations and interviews using a previously developed and published coding rubric. The interview data were analysed thematically to understand practitioners' experiences of using the new skills. Results: Practitioners demonstrated competence in embedding the skills into their routine practice following HCS training. They reflected on how patients liked being asked questions, the usefulness of setting SMARTER (Specific, Measured, Action-oriented, Realistic, Timed, Evaluated and Reviewed) goals and the power of listening. They could also identify facilitators of skill use and ways to overcome challenges such as patients with competing priorities and organisational constraints. They found the skills valuable as a way of empowering patients to make changes to manage their own health. Conclusions: HCS are acceptable to primary care practitioners, can be readily adopted into their routine consultations and are a helpful strategy for supporting patients to make changes. HCS training has the potential to be a sustainable, scalable and effective way of contributing to the prevention agenda by supporting disease self-management, and hence of addressing today's epidemic of lifestyle-related conditions.